Manipulation of oocyte maturation to improve porcine somatic cell nuclear transfer - Chen, Wenchao (2011)
Porcine somatic cell nuclear transfer (SCNT) offers new opportunities for fundamental science, medicine and agriculture. Ten countries or regions have developed the technology of porcine cloning and at least 42 groups have succeeded in producing piglets. Although successful, the efficiencies and reproducibility of porcine SCNT are extremely variable.